Strategi Internet Marketing Dalam Meningkatkan Volume Penjualan Usaha Skincare Gbee Glow Beauty (Perspektif Ekonomi Islam) - Sisqi Amelia; Bahtiar Effendi (UPT Penerbitan Universitas Jember, 2023)
This research was conducted to find out the internet marketing strategy in increasing the sales volume of the Gbee Glow Beauty skincare business according to the perspective of Islamic Economics and also aims to find out the problems faced in increasing the volume of business sales at Skincare Gbee Glow Beauty. This research includes field research (field research) using qualitative descriptive methods. The data collection techniques used in this research are observation and interview methods. The results showed that the internet marketing strategy carried out by Gbee Glow Beauty in increasing the sales volume of Skincare products was carried out through marketing on social media such as Facebook, WhatsApp, Instagram, and Shopee. In addition to maximizing through social media platforms, Gbee Glow Beauty also combines its marketing strategies through honest and excellent service strategies and competitive prices, good product quality, direct distribution channels, and massive online promotions. These efforts have proven to be able to increase consumer interest in buying Gbee Glow Beauty products.